Genome-wide identification and characterization of the Hsp70 gene family in allopolyploid rapeseed (Brassica napus L.) compared with its diploid progenitors - Liang, Ziwei; Li, Mengdi; Liu, Zhengyi; Wang, Jianbo (PeerJ, 2019)
Heat shock protein 70 (Hsp70) plays an essential role in plant growth and development, as well as stress response. Rapeseed (Brassica napus L.) originated from recently interspecific hybridization between Brassica rapa and Brassica oleracea. In this study, a total of 47 Hsp70 genes were identified in B. napus (AnAnCnCn genome), including 22 genes from An subgenome and 25 genes from Cn subgenome. Meanwhile, 29 and 20 Hsp70 genes were explored in B. rapa (ArAr genome) and B. oleracea (CoCo genome), respectively. Based on phylogenetic analysis, 114 Hsp70 proteins derived from B. napus, B. rapa, B. oleracea and Arabidopsis thaliana, were divided into 6 subfamilies containing 16 Ar-An and 11 Co-Cn reliable orthologous pairs. The homology and synteny analysis indicated whole genome triplication and segmental duplication may be the major contributor for the expansion of Hsp70 gene family. Intron gain of BnHsp70 genes and domain loss of BnHsp70 proteins also were found in B. napus, associating with intron evolution and module evolution of proteins after allopolyploidization. In addition, transcriptional profiles analyses indicated that expression patterns of most BnHsp70 genes were tissue-specific. Moreover, Hsp70 orthologs exhibited different expression patterns in the same tissue and Cn subgenome biased expression was observed in leaf. These findings contribute to exploration of the evolutionary adaptation of polyploidy and will facilitate further application of BnHsp70 gene functions.
Keywords: Hsp70 gene family; Brassica napus; Allopolyploidization; Orthologous pairs; Evolution